1994
DOI: 10.1071/mf9940889
|View full text |Cite
|
Sign up to set email alerts
|

Study of the ability of Daphnia carinata King to control phytoplankton and resist cyanobacterial toxicity: Implications for biomanipulation in Australia

Abstract: The properties of Daphnia carinata King as a grazer for use in biomanipulation trials were investigated. Mesocosm experiments suggested that in water from a lake where D. carinata was scarce, phytoplankton was nutrient-limited and the manipulated biomass of zooplankton had no effect on total chlorophyll a, whereas in water from a lake where D. carinata was dominant, nutrients were not limiting and total chlorophyll a was negatively correlated with the manipulated biomass of zooplankton. When offered lake phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 40 publications
2
71
0
Order By: Relevance
“…Others found differences in survival and growth among species and clones fed with microcystin-containing Microcystis cells (7,13,15). At least one paper reported an apparent resistance to microcystins (29). However, the observed differences in response to microcystins contained in solutions or cyanobacterial cells can have various causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others found differences in survival and growth among species and clones fed with microcystin-containing Microcystis cells (7,13,15). At least one paper reported an apparent resistance to microcystins (29). However, the observed differences in response to microcystins contained in solutions or cyanobacterial cells can have various causes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on survival tests with cyanobacterial cells and cell extracts, Jungmann (20) and Reinikainen (34) have, on the other hand, suggested that toxicity to Daphnia is not due to microcystins. Matveev et al (29) have even proposed an ineffectiveness of microcystins to harm Daphnia carinata, and Pflugmacher et al (33) have described an in vitro detoxification mechanism that, if also active in living Daphnia, may result in a resistance to microcystins.…”
mentioning
confidence: 99%
“…Likewise, copepods have been shown to be poor grazers of Nodularia (Sellner 1997), and in the Baltic Sea they appear to actively avoid consuming toxic cyanobacteria (Karjalainen et al 2007). Cladocerans, such as Daphnia spp., tend to be more generalist grazers than copepods (Boon et al 1994), and it is these that are often implicated in the reduction of toxic cyanobacteria (Matveev et al 1994). Even so, different members of the Daphnia genus have been shown to either enhance or reduce cyanobacterial growth (Fey & Cottingham 2011), and it cannot be assumed that the presence of cladocerans would lead to a reduction in Nodularia.…”
Section: Grazingmentioning
confidence: 99%
“…3) may have implications for toxicity toward grazing zooplankton. Since some daphnids, though notably not all (18), are sensitive to toxic strains of M. aeruginosa (28), it is conceivable that zooplankton could ingest a greater number of smaller Microcystis spp. cells, thus receiving a considerably larger dose of toxin.…”
mentioning
confidence: 99%